1976
DOI: 10.3758/bf03211993
|View full text |Cite
|
Sign up to set email alerts
|

Pain-elicited aggression in the squirrel monkey: An implicit avoidance contingency

Abstract: Squirrel monkeys were given either forward pairings of a bite-tube CS and shock US or backward pairings of these stimuli. Backward pairings produced stronger control of biting by the bite tube alone than did forward pairings. In a second experiment, subjects received backward pairings of US and CS with either a fixed ITI or a random IT!. Conditioned biting was obtained only when trials were presented with a fixed IT!. The magnitude of unconditioned biting was also significantly greater with the fixed IT!. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…We have also argued (Dunham & Carr, 1976) that the introduction of shock into a multiple-response repertoire can define certain responses as "safe" activities depending upon the temporal patterning of the shocks. Indeed, our use of the term "implicit avoidance rule" in reference to the increase in the most probable unpunished response during punishment implies that this behavior is fear motivated and maintained as an avoidance response (Dunham & Carr, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…We have also argued (Dunham & Carr, 1976) that the introduction of shock into a multiple-response repertoire can define certain responses as "safe" activities depending upon the temporal patterning of the shocks. Indeed, our use of the term "implicit avoidance rule" in reference to the increase in the most probable unpunished response during punishment implies that this behavior is fear motivated and maintained as an avoidance response (Dunham & Carr, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…I have discussed the implications of these rules for traditional punishment theory in other contexts (cf. Dunham, 1971;Dunham & Carr, 1976). In view of the fashionable contemporary trend toward arguing against the generality of empirical generalizations across species and responses, we have given first priority to considering the generality of these rules prior to elaborating further on the mechanisms which might underlie the rules.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments have shown that aggressive responding is classically conditionable in fish (Adler & Hogan, 1963;Thompson & Sturm, 1965), rats (Creer, Hitzing, & Schaeffer, 1966;Farris, Gideon, & Ulrich, 1970;Lyon & Ozolins, 1970;Vernon & Ulrich, 1966), and monkeys (Hutchinson, Renfrew, & Young, 1971). Although these effects have not always been strong (e.g., see Dunham & Carr, 1976), a conditioned stimulus (CS) that was followed by an unconditioned aversive stimulus (UCS) such as electric shock gradually came to produce aggressive responding similar to the aggressive responding that had initially occurred only after the UCS. Experiment I evaluated the possibility that aggressive responding might also develop along with conditioned suppression of a positively reinforced operant response by giving squirrel monkeys access to…”
mentioning
confidence: 99%